Physical disability and rehabilitation sourcebook : basic consumer health information about different types of disabilities, conditions leading to physical disability, housing, employment, supplemental security income, and transportation, and offers guidance on benefits for adults and children, social security disability insurance, tax exemption, coverage options and compensation, and financial assistance ; along with facts and rehabilitative and assistive technology and resources for additional help and information - Williams, Angela, 1963- (Disability series., 2020)
Provides an overview of the types of disability that limit an individual's physical functioning, mobility, dexterity, and stamina, either as a structural or functional impairment. The characteristics of specific physical disability are outlined and examples of the ways in which physical disability affects individuals are explained, along with information on how to find government and local disability programs and resources